Numerous intracystic floating balls as a sonographic feature of benign cystic teratoma: Report of 5 cases - Theera Tongsong (2018)
Objective. The purpose of this series was to describe the unusual but unique sonographic pattern of mature cystic teratoma. Methods. Five patients of reproductive age with clinical manifestations of a pelvic mass were evaluated with sonography for treatment planning. Results. All 5 cases showed the similar sonographic pattern of a large cystic tumor filled with multiple echogenic spherical structures floating in the cystic background. Of the 5 patients, 3 had rather large balls varying in size between 1 and 4 cm in the same tumor masses, whereas the other 2 had numerous smaller balls of about 0.5 cm in diameter. The numerous crowded very small echogenic balls in the last 2 cases mimicked solid nodules representing malignancy. However, there was no vascularization in the balls, which suggested a benign nature. The postoperative pathologic diagnosis was mature cystic teratoma without any malignant component in all cases. Conclusions. The sonographic feature of intracystic floating echogenic balls is probably pathognomonic for mature teratoma and is easily detected in most cases. Color Doppler sonography is helpful in differentiating these benign nodules (small balls) from malignant tumors. © 2006 by the American Institute of Ultrasound in Medicine.